2015
DOI: 10.1155/2015/740794
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Accumulation of Curcumin in Microrhizomes ofCurcuma aromaticaSalisb

Abstract: Curcuminoids, and mainly curcumin, are potential therapeutic agents for the prevention of various diseases; however, little is known about the factors that influence their accumulation in Curcuma species. In this study, the effects of factors such as sucrose concentration, different ratios of 6-benzylaminopurine (6-BA) and α-naphthalene acetic acid (NAA), and light quality on the accumulation of curcumin and other curcuminoids in Curcuma aromatica were investigated. Microrhizomes grown on media containing 3% s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…The previous study showed that proper concentration mepiquat chloride (DPC) could increase fresh weight of scutllaria baicalensis roots, enhanced the contents of baicalin and total flavonoids, but deduced the contents of baicalein and wogonin compared with CK (Hu et al, 2012). Compared with CK, a 3% sucrose medium added 3.0 mg/L 6-BA and 0.5 mg/L NAA enhanced the contents of curcumin and curcuminoids in imcrorhizomes of curcuma aromatica salisb which exposures to red light (Wu et al, 2015, Ong et al, 2017). Different concentrations of 6-BA or 6-BA and NAA combination significantly inhibited the growth of Pueraria phasedoides hairy roots, and reduced biomass and total content of isoflavone, but NAA inhibited the growth and accumulation of medicinal ingredient of Polygonum multiflorum hairy roots (Yu et al, 2006, He and Shi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The previous study showed that proper concentration mepiquat chloride (DPC) could increase fresh weight of scutllaria baicalensis roots, enhanced the contents of baicalin and total flavonoids, but deduced the contents of baicalein and wogonin compared with CK (Hu et al, 2012). Compared with CK, a 3% sucrose medium added 3.0 mg/L 6-BA and 0.5 mg/L NAA enhanced the contents of curcumin and curcuminoids in imcrorhizomes of curcuma aromatica salisb which exposures to red light (Wu et al, 2015, Ong et al, 2017). Different concentrations of 6-BA or 6-BA and NAA combination significantly inhibited the growth of Pueraria phasedoides hairy roots, and reduced biomass and total content of isoflavone, but NAA inhibited the growth and accumulation of medicinal ingredient of Polygonum multiflorum hairy roots (Yu et al, 2006, He and Shi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Tuber formation, size and fresh weight in acclimatized plantlets of yam under 3% sucrose was maximized after transplanting for 60-120 day (Ovono et al 2009), whereas 6% sucrose or 8% maltose was required for cocoyam (Xanthosoma sagittifolium) for mini-tuberization (Djeuani et al 2014). The secondary metabolites, BIS, DEM and CUR, in mini-rhizomes of wild turmeric plantlets acclimatized under 3% sucrose were highest, whereas micro-rhizome formation (>50%) and fresh weight (>0.025 g) were maximized in 5-9% sucrose (Wu et al 2015). In cassumunar ginger (Zingiber montanum), phenolic, flavonoid, tannin, alkaloid, saponin and steroid in induced micro-rhizomes using 6% sucrose were enriched over the natural rhizomes, whereas curcuminoid content was equal with natural rhizomes (Rajkumari and Sanatombi 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Regarding disease resistance, several genes were identified that play various roles in broad pathogen resistance including R gene-mediated resistance, oxidative stress, and systemic acquired resistance: HIN1/NDR1 , lipase , NAC28 , UDP-glycosyltransferase , cysteine-rich RLK , and cytochrome p450 [ 24 , 45 , 47 , 60 , 70 , 71 , 72 ]. None of these factors were specifically antiviral except for AtNAC28 , which restricts TCV infection.…”
Section: Resultsmentioning
confidence: 99%